Industrial RuO2‐Based Deacon Catalysts: Carrier Stabilization and Active Phase Content Optimization. Issue 3 (7th February 2013) - Amrute, Amol P.; Mondelli, Cecilia; Schmidt, Timm; Hauert, Roland; Pérez‐Ramírez, Javier
Abstract RuO2/SnO2–Al2O3 has been recently reported as an industrial catalyst for Cl2 production through HCl oxidation. The stabilizing role of the alumina binder in the material, essential for its durable performance, is elucidated here. Al2O3 prevents chlorination of the SnO2 carrier under relevant reaction conditions, whereas, in its absence, SnO2 losses exceed 80 wt % in very short times owing to volatilization as SnCl4. Characterization by using X‐ray diffraction, temperature‐programmed reduction with hydrogen, and high‐resolution TEM indicates expansion of the cassiterite cell in the SnO2–Al2O3 composite with respect to pure SnO2, which suggests the insertion of certain Al species upon mechanochemical and thermal activation of the oxide mixture. 27Al magic‐angle spinning NMR and X‐ray photoelectron spectroscopy studies reveal that the pentahedrally coordinated Al3+ cations interact with SnO2, generating an electron‐depleted region near the surface of SnO2 particles. This induces some acidic character in cassiterite, which possibly makes it inert toward HCl. Besides this electronic effect, the presence of thin porous amorphous alumina films, partly covering the SnO2 surface, can offer additional geometric protection of the support. Mechanical mixing followed by calcination is essential to attain stabilization, and maximized effects are achieved with a high‐surface area alumina. Other oxides such as SiO2 are ineffective in preventing tin losses during HCl oxidation. The practical implications of these findings are very important. The metal loading (fourfold decrease) and, thus, the cost of the catalyst can be significantly lowered without compromising its long‐term stability.